AN ANALYSIS OF MENTAL PROCESS IN MILK AND HONEY POEMS COLLECTION BY RUPI KAUR - Tiara Nugi Fitriafi (LPPM STKIP PGRI Bandar Lampung, 2021)
The study of SFL in the form of poem becomes an object in this study. This study will apply one of the scopes of SFL in Milk and Honey poems collection. This study examines the mental process in Milk and Honey poems collection. The purposes of this study are (1) to identify the kinds of mental process in Milk and Honey poems collection, (2) to explain the way the author represents the kinds of mental process in Milk and Honey poems collection. This study uses theory from Halliday and Matthiessen (1999). According to that theory, mental process is divided into three types: cognition, affection, and perception. The analysis shows that cognition and perception dominate the author’s representation in Milk and Honey poems collection, while affection is the least types appeared in this poems collection.